Elucidating the resistance repertoire, biofilm production, and phylogenetic characteristics of multidrug‐resistant Escherichia coli isolated from community ponds: A study from West Bengal, India. (20th January 2022) - Bhattacharyya, Debaraj; Banerjee, Jaydeep; Habib, Md; Thapa, Geetanjali; Samanta, Indranil; Nanda, Pramod Kumar; Dutt, Triveni; Sarkar, Keka; Bandyopadhyay, Samiran
Abstract: This study details about the phenotypic and molecular characteristics of multidrug‐resistant (MDR) Escherichia coli in the fresh community pond water ( n = 257) collected from three districts of West Bengal, India. In total, 57 isolates were MDR of which 38 emerged as extended spectrum and 7 as Amp C‐type β‐lactamase producers in phenotypic assay. Among β‐lactamase genes, bla CTXM‐1was predominant (87.71%) followed by bla AmpC (77.2%) and bla TEM‐1 (22.8%). Six MDR strains carried metallo‐β‐lactamase (MBL, bla NDM‐1) gene. Tissue culture plate assay confirmed strong biofilm (SP) production in four MDR and one non‐MDR isolates. In PCR‐based replicon typing (PBRT), multiple plasmids of diverse replicon types (Frep, FIB, I1, FIA, K/B, HI1, and Y) were identified. The enterobacterial repetitive intergenic consensus–polymerase chain reaction (ERIC‐PCR)‐based phylogenetic analysis revealed a high degree of genetic divergence among the MDR isolates. Multiplex PCR‐based phylogrouping categorized 11 isolates as virulent (B2/D/F), which carried bla CTXM‐1 gene and three had bla NDM‐1 gene. Relative transcriptional activity of Acr AB efflux pump was significantly elevated among the SP and MBL producers. The presence of MDR E. coli isolates, particularly those resistant to carbapenem, in pond water used for daily domestic and household work, is a cause of concern as these pathogens may sneak into human food chain causing life‐threatening infections. Practitioner Points: Multidrug‐resistant biofilm producing E. coli isolated from community pond water. A few of them were carbapenem‐resistant and belonged to virulent (B2/D) types. Expression of Acr AB efflux pumps was found significantly elevated among biofilm producers and carbapenem‐resistant population. Abstract : Fresh pond water harboured MDR, biofilm producing E. coli . Frequent resistance to tetracycline, cephalosporins and quinolone was noted. Majority were ESBL producers and a few belonged to virulent (B2/D) type.